Total Protein Value Of Stray Cats And Domestic Pet Cats In Surabaya City - Intan Permatasari Hermawan; Era Hari Mudji (Universitas Syiah Kuala, 2022)
The purpose of this research was to identify the protein value of stray cats and domestic pet cats in Surabaya. In this study blood samples were collected from 28 stray cats and 28 domestic pet cats. Total protein value was determined by Pacar Laboratory Surabaya. The result showed that 11 samples of stray cats (39%) had abnormal protein value, where 7 samples had low protein level (4,5-4,7g/dL) and 4 samples had high protein level (9,1-10,1 g/dL). Total protein value from domestic pet cats showed that 7 samples (25%) were abnormal in which 4 samples had low protein level (5,3-5,8 g/dL) and 3 samples had high protein level (8,9-9,4 g/dL). The data was analysed using independent sample t-test with SPSS, and showed that the data was not significantly different between stray cats and domestic pet cats. It can be concluded that both stray cats and domestic pet cats had risk of low and high total protein value as indicators of any disease.